2021
DOI: 10.3389/fimmu.2021.557433
|View full text |Cite
|
Sign up to set email alerts
|

Antagonism of Protease Activated Receptor-2 by GB88 Reduces Inflammation Triggered by Protease Allergen Tyr-p3

Abstract: The occurrence of allergic diseases induced by aeroallergens has increased in the past decades. Among inhalant allergens, mites remain the important causal agent of allergic diseases. Storage mites- Tyrophagus putrescentiae are found in stored products or domestic environments. Major allergen Tyr-p3 plays a significant role in triggering IgE-mediated hypersensitivity. However, its effects on pulmonary inflammation, internalization, and activation in human epithelium remain elusive. Protease-activated receptors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 76 publications
0
13
0
Order By: Relevance
“…On the other hand, Par2 activation protected against myocardial ischemia-reperfusion [ 41. ], as well as aggravated epithelial inflammation [ 42. ].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, Par2 activation protected against myocardial ischemia-reperfusion [ 41. ], as well as aggravated epithelial inflammation [ 42. ].…”
Section: Introductionmentioning
confidence: 99%
“…7,26 For mites, junctional complexes in the airway epithelium also undergo indirect proteolysis which may be PAR-dependent. 6,7,15,34 A recent study showed that the fungal allergen Asp f 13 damaged airway epithelial TJ and E-Cadherin (AJ).…”
Section: Prote a S E Allerg En S And Tissue Barrier Perme Ab Ilit Ymentioning
confidence: 99%
“…[3][4][5][6] However, this process is prevented by specific 6,7 and non-specific protease inhibitors, [6][7][8][9][10][11][12] or inhibitors of signaling pathways activated by protease allergens. [13][14][15][16][17][18] Furthermore, the addition of a protease to an enzymatically inactive protein can render that protein allergenic. 4,10,[19][20][21] Thus, not only does protease activity endow an allergen with its adjuvant activity, but it also acts as an exogenous allergic adjuvant for other inert or otherwise not allergenic proteins.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, a small molecule antagonist, GB83, exerted harmful effects on colon epithelial cells by decreasing the expression of autophagy- and TJ-related factors and increased permeability [ 234 ]. In contrast, inhibition of the PAR 2 pathway by GB88 in lung epithelial cells [ 235 ] or using I-191 in arterial endothelial cells [ 236 ] moderated actin rearrangement and TJ disruption and reduced the permeability of the cellular monolayers. Moreover, a non-peptidic PAR 2 ligand, the full agonist AC-55541, ameliorated the IL-17-induced loss of epithelial resistance in brain microvascular endothelial cells [ 237 ].…”
Section: Zonulin Pathway As a Therapeutic Targetmentioning
confidence: 99%